The effect of structure on improvement of the PNA Young modulus: A study of steered molecular dynamics. (December 2019) - Ghasemi, Reza Hasanzadeh; Keramati, Masoud; Mojarrad, Mohammad Hashemi Saleh
Graphical abstract: Highlights: Wild-type PNA exhibits lower Young's modulus in contrast to mutated PNAs. Changes are made on PNAs in order to Improve Young's modulus. Stability of each Prefoldin tentacles in different stretching conditions is almost equal. Abstract: Prefoldin is a molecular chaperone and acts as a nano-actuator in cargo carriage and drug delivery for disease treatment. Investigating the mechanical properties of nano-actuator helps predict its behavior and measure its performance under various environmental conditions, like external forces that are applied. Accordingly, this paper investigates the elastic properties of the Prefoldin nano-actuator (PNA), specifically its Young modulus and the structural changes on a microscopic scale. For this purpose, three structurally different PNAs obtained from Protein Data Bank (PDB) and previous studies of our research team have been used. The selected three-tentacles Prefoldin are analyzed via the series of steered molecular dynamics simulations (SMD) based on the theory of Two Springs in Series. The simulation is applied in the velocity of 0.1, 0.05, and 0.01. Due to differences in the structure of the Prefoldin, PNAs exhibited different behaviours at various pull rates. Also, the analysis showed different values of Young's modulus for the PNA tentacles in the interval of (2.5–4 GPa). Understanding the mechanical properties of a Prefoldin nano actuator allows for a closer examination of its application in transportation the pathogenic cargos and intelligent drug delivery.